การสะท้อนภาพของเหตุการณ์ที่เกี่ยวกับชาวมุสลิมในหนังสือพิมพ์ไทย - ธีระยุทธ ลาตีฟี (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The study focused on the portrayal of Muslims in the Thai-language newspapers to find out how the image of muslims, who are a minority group in Thailand, was presented and if stories were slanting. To this end, news and articles about Muslims, both at home and in foreign locations, were analyzed. The items were taken from four dailies: Thai Rath, Daily News, matichon and Thai Post between January 1, 1998 and December 31, 1998. The findings are as follows: 1. Most of the Muslims events were news reports printed in the foreing news section. They rarely appeared as lead stories and were mostly found in the inside pages. Among the stories covered involved social problems, social disturbances, crimes, sabotage, conflicts, military exercises as well as local and international politics. The newspapers put more emphasis on the negative aspects of the news which were usually accompanied by one of the following elements: oddity, conflict, mystery, and sensation. Most of the events occurred in Southeast Asia and the Middle East. 2. The newspapers relied more on Western or other news sources than Muslim sources or Muslim mass media 3. The newspapers tended to portray more of the negative aspects of the news involving Muslims. 4. The Unfavorable images of Muslims were more prevalent in the newspapers. Muslims were usually portrayed as 1) terrorists/saboteurs/Muslim fundamentalists; 2) rioters/mobs/demonstrators; 3) violators/non-conformists/breakers of agreements; 4)buyers of powerful weapons; and 5) victims of severe economic crises.